Ouvrir la porte à des pratiques euthanasiques? Pas aussi simple que les Rapports de la Société royale, du Barreau du Québec et de la Commission spéciale sur le mourir dans la dignité le laissent croire - Saint-Arnaud, Jocelyne (BioéthiqueOnline, 2013)
The Royal Society of Canada, the Bar of Quebec and the Special Commission on Dying with Dignity took position in favour of voluntary euthanasia. The Quebec government has prepared a draft bill in which voluntary euthanasia can be considered as an option in end-of-life care. This bill aims to define regulatory guidelines that, if followed, will protect medical doctors from lawsuits. The main argument supporting this project is based on respect for autonomy. This article argues that other values, such as pursuit of the common good, ought also to be taken into account. This article describes the experience of the Netherlands to show that a slippery slope is possible and that legal measures do not necessarily bring more transparency in medical practices concerning euthanasia. Prudence requires that adequate palliative care be accessible for all before defining legal measures on voluntary euthanasia.